FAKTOR-FAKTOR YANG MEMPENGARUHI PERSEPSI WAJIB PAJAK MENGENAI PENGGELAPAN PAJAK (TAX EVASION) DIKPP PRATAMA SEMARANG CANDISARI (Students' Journal of Accounting and Banking, 2015)
This study aimed to analyze Factors Influencing Perceptions Regarding tax fraud Taxpayers (Tax Easion). This research was conducted in Semarang Candisari STO. The population in this study are all the individual taxpayer in Semarang Candisari STO. The sample in this study were 110 respondents. The sampling method was convenience sampling. Methods of data collection is done by questionnaire. Engineering test data used in this study include test validity by factor analysis, reliability tests with Cronbach Alpha. Classical assumption test, multiple linear regression analysis, t test to test and prove the research hypothesis. The results show that the justice system of taxation, discrimination and service quality significantly influence tax evasion (tax evasion).Keywords: Justice, Taxation System, Discrimination, Quality Of Service and Tax Evasion